Line fault indicator for sabah rural distribution network - Amri Aliaman, Zarinah (2022)
Due to Sabah’s mountainous landscape, it is very challenging to provide electrification to rural area. Distribution systems are continuously exposed to fault occurrences due to various reasons, such as lightning strike, failure of power system components and etcetera. However, due to the long-distance distribution overhead lines often causing longer restoration time. Therefore, the concept of Line Fault Indicator would be beneficial for early ground fault detection which leads to fast fault clearance. The objective of this project is to inspect the ability of line fault indicator to react to overhead lines permanent faults. The analysis of the line’s fault current will be conducted using CAPE software and it will be compared to the operational characteristics of the neon bulb of line fault indicator. Result from this simulation showed the relationship of neon bulb and fault’s current characteristic for overhead permanent faults and provides assurance that the indicator is properly functioning in locating the faulted lines.